The Influence of Jakarta–Rotterdam City Diplomacy on Flood Management Policy (2016–2024) - Putri Mayang Rembulan; Aditya Akbar Pratama (Social Science Research Journal, 2025)
Abstract. This study analyzes the influence of city diplomacy between Jakarta and Rotterdam on flood management policy in Jakarta during the 2016–2024 period. The research focuses on how intercity cooperation affects the formulation and implementation processes of public policies in flood management. The main objective is to identify the contribution of city diplomacy in supporting adaptive and sustainable environmental policies. The study employs a descriptive qualitative method using a case study approach and document analysis. The findings reveal that the Jakarta–Rotterdam cooperation has generated positive impacts, including the strengthening of institutional capacity, the enhancement of water management technology, and the adoption of nature-based approaches in urban drainage systems. The study concludes that city diplomacy serves as a strategic instrument in the development of public policy, provided that long-term commitment, sustained collaboration, and active engagement of local actors are ensured. Keywords: city diplomacy; flood governance; Jakarta–Rotterdam cooperation; public policy; urban climate resilience Abstrak. Penelitian ini menganalisis pengaruh diplomasi kota antara Jakarta dan Rotterdam terhadap kebijakan penanganan banjir di Jakarta selama periode 2016–2024. Fokus kajian terletak pada bagaimana kerja sama antarkota memengaruhi proses formulasi dan implementasi kebijakan publik dalam pengelolaan banjir. Tujuan penelitian ini adalah mengidentifikasi kontribusi diplomasi kota dalam mendukung kebijakan lingkungan yang adaptif dan berkelanjutan. Metode yang digunakan adalah kualitatif deskriptif dengan pendekatan studi kasus dan analisis dokumen. Hasil penelitian menunjukkan bahwa kerja sama Jakarta–Rotterdam memberikan dampak positif berupa penguatan kapasitas kelembagaan, peningkatan teknologi pengelolaan air, serta penerapan pendekatan berbasis alam dalam sistem drainase perkotaan. Penelitian ini menyimpulkan bahwa diplomasi kota berperan sebagai instrumen strategis dalam pembentukan kebijakan publik, dengan prasyarat adanya komitmen jangka panjang, keberlanjutan kerja sama, serta keterlibatan aktif aktor lokal. Kata Kunci: diplomasi kota; tata kelola banjir; kerja sama Jakarta–Rotterdam; kebijakan publik; ketahanan iklim perkotaan